2015
DOI: 10.1089/cap.2015.0066
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Nonemotional Conflict Processing in Pediatric and Adult Anxiety Disorders

Abstract: The current study of youth and adults did not replicate prior behavioral findings of failure to engage conflict adaptation in anxiety disorders. Therefore, more work is needed before widely adopting conflict adaptation paradigms as a standard neurocognitive marker for anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Correlational evidence for the affect ► control link Some studies have suggested that sequential congruency effects are increased for participants with high anxiety (Booth & Peker, 2017;Larson, Clawson, Clayson, & Baldwin, 2013). However, this link between the sequential congruency effect and anxiety has not been replicated by others (A. L. Gold, Jarcho, Rosen, Pine, & Ernst, 2015;Krug & Carter, 2010;Osinsky, Alexander, Gebhardt, & Hennig, 2010;Osinsky, Gebhardt, Alexander, & Hennig, 2012). The results for mood disorders are also mixed.…”
Section: Conflict-triggered Affect Drives Control Adaptation-the Affementioning
confidence: 99%
“…Correlational evidence for the affect ► control link Some studies have suggested that sequential congruency effects are increased for participants with high anxiety (Booth & Peker, 2017;Larson, Clawson, Clayson, & Baldwin, 2013). However, this link between the sequential congruency effect and anxiety has not been replicated by others (A. L. Gold, Jarcho, Rosen, Pine, & Ernst, 2015;Krug & Carter, 2010;Osinsky, Alexander, Gebhardt, & Hennig, 2010;Osinsky, Gebhardt, Alexander, & Hennig, 2012). The results for mood disorders are also mixed.…”
Section: Conflict-triggered Affect Drives Control Adaptation-the Affementioning
confidence: 99%
“…Steinhauser et al (2016) found that the emotional conflict adaptation effect was only present if the previous response conflict was low; however, no overall effect was established. Jiang et al (2020), Hua et al (2021), Gold et al (2015), and Krug and Carter (2012) did not find a significant conflict adaptation effect in reaction time outcome measures. In contrast, Jarcho et al (2013), Irmen et al (2017), Chechko et al (2014), O.…”
Section: Resultsmentioning
confidence: 70%
“…At any rate, multiple studies described their findings in the context to conflict resolution, despite not testing for it in their data. It is also important to note that—based on the systematic review—the effect appears to be only present in healthy participants but not in most tested clinical populations (e.g., Gold et al, 2015; Krug & Carter, 2012; Saunders & Jentzsch, 2014), which may explain why our previous work was unable to replicate the emotional conflict resolution effect using this task (Perini et al, 2023).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations